5
$\begingroup$

Let $S_{k},$ where $k=1,2,3,\cdots \cdots ,100$ denote the sum of the infinite geometric series whose first term is $\displaystyle \frac{k-1}{k!}$ and the common ratio is $\displaystyle \frac{1}{k},$ then the value of $\displaystyle \frac{100^2}{100!}+\sum^{100}_{k=1}|(k^2-3k+1)S_{k}|$ is

$\displaystyle S_{k} = \frac{a}{1-r} = \frac{(k-1)\cdot k}{k!\cdot (k-1)} = \frac{1}{(k-1)!}$

So $\displaystyle \sum^{100}_{k=1}\bigg|(k^2-3k+1)S_{k}\bigg| = \sum^{100}_{k=1}\bigg|\frac{(k-1)^2-k}{(k-1)!}\bigg| = \sum^{100}_{k=1}\bigg|\frac{(k-1)}{(k-2)!}-\frac{k}{(k-1)!}\bigg| $

wan,t be able to go further, could some help me with this, thanks

$\endgroup$
2
$\begingroup$

Hint thats a telescpoic series thus only first and last terms survive so summation is $|1-\frac {100}{99!}| $ also starting series with $k=2$ makes sense as i dont know whether value of $(-1)!$ is defined

| cite | improve this answer | |
$\endgroup$
2
$\begingroup$

$$\frac{k-1}{(k-2)!}-\frac{k}{k!}=\frac{(k - 2) k^2}{k!}>0 \implies \bigg|\frac{(k-1)}{(k-2)!}-\frac{k}{(k-1)!}\bigg|=\frac{(k-1)}{(k-2)!}-\frac{k}{(k-1)!}$$

Then as @Archis said use telescoping sum.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.